President Jaruzelski’s relations with the USSR as an element of Poland’s Eastern policy in the period of 1989–1990 (Economic and Political Thought, 2018)
Thanks to the archival sources that have not been used so far, the articleprovides an opportunity to look at the mechanism of freeing Poland and, ina broader perspective, other countries that have been under the Soviet influencesince Yalta, from the hegemony of the USSR. Against this background,it presents the opinions and intentions of the communists who lost power asa result of the election of 4 June 1989. They pinned their hopes on WojciechJaruzelski, the President whom the amended Constitution gave great powers.However, life showed that he could have exercised them only for the price ofthe country division, a conflict that would have led to chaos instead of reforms,a breakdown instead of strengthening Poland’s position on the internationalarena. It would have strongly established Jarulelski’s negative image, too.The President faced a dilemma: support changes, including those that weregeopolitical in nature, or oppose them. Having recognised the interest of thestate and the will of the citizens expressed in the election, he chose the firstoption. However, it must be said that his weakening political position playedan important role. The presidential ballot won by one vote, systematic eliminationof the PUWP representatives from posts in the coalition government,the collapse of PUWP, public opinion dislike – all these things deprived himof tools to act. In the relations with the USSR, he adopted a role of a buffer.Until the end of his term of office, however, he believed in the success of theSoviet perestroika and Gorbachev as a reformer of the system, which wouldcontinue existing after the transformation. That is why he wanted to supportGorbachev and use him as a guarantor of democracy at home as well as ininternational relations. He was afraid of the USSR’s turn to nationalism androwdy imperialism. He could not realise Poland’s turn from the East to theWest, accession to NATO and the European Communities. However, he didnot undertake any steps that might have destroyed those plans.
Keywords: President, Wojciech jaruzelski, Eastern policy, Poland – history